EVALUASI LAYANAN KAWIN, LAHIR, MATI, PINDAH, DATANG (KLAMPID) PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA SURABAYA - Hafshah Vitri Tarantika; Suci Megawati (Publika, 2022)
Public service is a series of activities provided by public service providers (government) in order to meet a community's needs in accordance with statutory regulations. The Department of Population and Civil Registration of the City of Surabaya is the service agency that is most needed in the context of administering the launch of an innovation, Married, Born, Died, Moved, Came (KLAMPID), which is an online service system in the field of population. After several years of implementation, it is necessary to make improvements, taking into account the evaluations that have been obtained from the community. The research method uses a descriptive approach and data collection techniques through observation and interviews with the Surabaya City Population and Civil Registry Office. The results of the study indicate that the implementation of KLAMPID on the effectiveness criteria of KLAMPID is said to be quite effective but not optimal in website operations. KLAMPID efficiency is very efficient in public services. The KLAMPID assessment criteria are quite satisfactory and satisfying to the community, so they are evenly distributed among residents of Surabaya and outside Surabaya. Then, on the responsiveness criteria of the KLAMPID system, the response is good for users, but there are still complaints about errors on the website, and the accuracy criteria are correct but have not fully reached the public. So the researchers suggest that the data refine and update the system in order to anticipate technical problems. Keywords: Evaluation, KLAMPID (Married, Born, Died, Moved, Came), Population Service